The Strategist of Micro, Small and Medium Brazilian Private Company - Fontes Filho, Joaquim Rubens; Nunes, Geraldo Sant Anna (Review of Business Management, 2010)
The importance of micro, small and medium size companies (MSMC) to the economical development and job creation in the country hasn’t found parallel with respect to the production of theories in the strategy field, even considering the limited capacity of action of the MSMCs and the idiosyncrasies of their leaders. This article seeks to contribute to the understanding of the strategy formation processes in these companies by the nature of the strategic thinking of their strategists, having as reference the taxonomy of generic strategies and the cognitive processes of decision making and strategic thinking. It aims at proposing a typology to comprehend the nature of strategic thinking of these managers, identifying their main characteristics dimensions and proposing an instrument that allows its categorization and comparison. The application of a survey with an intentional sample composed by 70 strategists allowed the use of factor analysis for the construction of categories and scale, and the observation that, in the universe of the surveyed strategists in regard to their way of thinking, intuition is complementary, not dominant, the collective character is intense in the strategy formation process as well as the appreciation of formalism and belief of the importance of planning and registering their intentions. Key words: Strategy. Micro, small e medium companies. Intuition. Collective character. Formalism.